CONTENT OF CADMIUM (CD) AND LEAD (PB) IN SEDIMENTS AND ORGANISMS (GREEN MUSSEL PERNA VIRIDIS LINNAEUS AND OYSTER CRASSOSTREA GIGAS THUNBERG) AT VUNG THUNG, DA NANG CITY - Khanh, Nguyen Van; Minh, Vo Van; Vinh, Tran Duy (Vietnam Journal of Marine Science and Technology, 2014)
Through 2 sampling times (March and August, 2011), the results of analyzing content of Cd and Pb in sedimentary samples indicated the signs of heavy metal pollution (Cd and Pb) in Vung Thung area, Da Nang city. Specifically, Cd content ranged from 0.54 to 1.58mg/kg (dry weight), some sediment samples was from 1.23 to 2.26 times higher than TEL (threshold effect level; < 0.7mg/kg dry weight) of ISQGs (Interim marine sediment quality guide-lines, Canada). Concerning to Pb, its content was in the range of 18.37 - 87.29mg/kg (dry weight), of which most samples were from 1.13 to 2.74 times as high as TEL (≤ 30.3mg/kg dry weight). In regards to heavy metal content in tissue of oyster and green mussel, cadmium content in both of two species was lower than standard (≤ 2mg/kg wet weight) of Ministry of Health (QCVN 8-2:2011/BYT), however, lead content accumulated in oyster is from 2.21 to 2.56 times higher than the allowed limit of Ministry of Health (≤ 1.5mg/kg wet weight), in green mussel was from 1.01 to 3.28 times as much as the allowed limit. The results from correlation analysis showed that the correlation between cadmium in sediment and in tissues of both species was weak, but Pb content in sediment correlated significantly with Pb content in tissues of both species, specifically, correlation coefficient was equal to 0.76 within oyster and 0.72 within green mussel. Indeed, oyster and green mussel can be used as bio - monitoring to evaluate lead pollution in marine environment.